Single-session upper limb plyometric training is as effective as two sessions for improving muscle strength, power, and serve velocity in male youth tennis players: a randomized parallel controlled study - Wang, J.; Xu, Q. (Frontiers in Psychology, 2025)
Introduction: Providing a balanced training stimulus that promotes positive adaptations without excessively increasing training volume—and thereby avoiding disruptions to the training process—is a challenging task for strength and conditioning coaches. This study aimed to compare the effects of one vs. two weekly sessions of upper limb plyometric training (ULPT) on muscle strength, power, and serve velocity in male youth tennis players.